Long-interval intracortical inhibition in primary motor cortex related to working memory in middle-aged adults - Redondo-Camós, María; Cattaneo, Gabriele; Alviarez-Schulze, Vanessa; Delgado-Gallén, Selma; España-Irla, Goretti; Solana-Sanchez, Javier; Perellón-Alfonso, Ruben; Albu, Sergiu; Tormos, José M.; Pascual-Leone, Alvaro; Bartres-Faz, David (Frontiers in Psychology, 2022)
Introduction: Excitability of the primary motor cortex measured with TMS has been associated with cognitive dysfunctions in patient populations. However, only a few studies have explored this relationship in healthy adults, and even fewer have considered the role of biological sex. Methods: Ninety-seven healthy middle-aged adults (53 male) completed a TMS protocol and a neuropsychological assessment. Resting Motor Threshold (RMT) and Long-Interval Intracortical Inhibition (LICI) were assessed in the left motor cortex and related to attention, episodic memory, working memory, reasoning, and global cognition composite scores to evaluate the relationship between cortical excitability and cognitive functioning. Results: In the whole sample, there was a significant association between LICI and cognition; specifically, higher motor inhibition was related to better working memory performance. When the sample was broken down by biological sex, LICI was only associated with working memory, reasoning, and global cognition in men. No associations were found between RMT and cognitive functions. Conclusion: Greater intracortical inhibition, measured by LICI, could be a possible marker of working memory in healthy middle-aged adults, and biological sex plays a critical role in this association.